Synthesis and biological evaluation of (3-arylisoxazol-5-yl) methyl 6-fluoro-4-oxo-4H-chromene-2-carboxylates as antioxidant and antimicrobial agents - Battula Kumaraswamy; Narsimha Sirassu; Nagavelli Vasudeva Reddy; Srinivasa Rao Mutheneni (Journal of the Serbian Chemical Society, 2017)
A series of novel (3-aryl-1,2-oxazol-5-yl) methyl 6-fluoro-4-oxo-4H- -chromene-2-carboxylate derivatives (C1-C12) were synthesized by Cu (I) catalyzed reaction of in situ generated nitrile oxides with prop-2-yn-1-yl 6-fluoro-4-oxo-4H-chromene-2-carboxylate in good yields and investigated their antioxidant and antimicrobial activities. Among all the synthesized compounds, C1 (IC50: 16.43 ± 0.57 μM) and C12 (IC50:15.98 ± 0.72 μM) have registered good antioxidant activity as compared to the standard drug Trolox. Compound-C1, C3, and C6 have registered very good inhibition against all gram-positive and gram-negative bacterial strains with MIC values ranging from 9.375 to 37.5 (μg mL-1). Compound-C7, C8, C9, C10, and C11 have registered good inhibition against B. subtilis and S. aureus with MIC values ranging from 18.75 to 37.5 (μg mL-1). Compound-C10 and C11 against P. aero-ginosa have shown prominent activity than the standard drug Penicillin (MIC: 12.5 μg mL-1) with MIC 9.375 μg mL-1 (~ 1.33 fold potent than Penicillin). Compound-C7, C8, and C9 have registered good to moderate antifungal activity against four tested fungal strains with MIC values ranging from 18.75 and 37.5 μg mL-1